Ultrafast formation of porosity and heterogeneous structures on 2D oxides via momentary photothermal effect - Ahrom Ryu; Bo-In Park; Hyun-Jae Lee; Jung-Won An; Jeong-Jun Kim; Sahn Nahm; Seong H. Kim; Byungju Lee; Ji-Won Choi; Jang, Ji Soo (Royal Society of Chemistry, 2025)
2D metal oxides have attracted significant interest in numerous scientific research fields owing to their exceptional physicochemical properties derived from unique crystal structures and surfaces. However, unfortunately, there are still challenges to achieving fast and sensitive chemical sensing using 2D metal oxides due to their poor surface porosity. Here, a simple but powerful synthetic method for highly porous as well as reduced 2D metal oxides is suggested through a 2D oxide exfoliation approach combined with flash-thermal shock (FTS). The molecular thick-level 2D Ti0.87O2 nanosheets are simply synthesized by ion-exchange exfoliation and a subsequent ultra-fast FTS (7.5 ms) process, resulting in simultaneous formation of uniform pores and reduced Ti0.87O2-x on the 2D Ti0.87O2 surface. In this process, the heterojunctions play a crucial role in enhancing the sensitivity by facilitating charge transfer and improving the electrical properties. Density functional theory calculations and ex situ TEM analysis elucidate that the fast phase transformation of 2D Ti0.87O2 is a key driving force of porosity and reduced Ti0.87O2-x formation. Based on these features, porous 2D Ti0.87O2 exhibits an exceptional HCHO sensing characteristic including outstanding reversibility and sensitivity even at room temperature.